S122 The effect of body mass index on patient outcome in chronic obstructive pulmonary disease: a retrospective cohort study using the Hampshire Health Record. (12th November 2015) - Perry, C; Josephs, L; Johnson, M; Gulliford, D; Thomas, M
Abstract : Introduction and objectives: Chronic obstructive pulmonary disease (COPD) is a systemic disease characterised by persistent airflow obstruction but also has significant extra-pulmonary manifestations, including effects on body mass index (BMI). Nutritional status has been implicated as a predictor of outcome. We aimed to investigate the relationship between BMI and outcomes in a representative sample of UK COPD patients. Method: Patients with a coded GP diagnosis of COPD on or before 31/12/2010 and full data for 3 years or until death were identified from the Hampshire Health Record Analytical database, which collects anonymised routine clinical care data from GP and hospital computer records. Subjects were categorised as underweight, normal, overweight, obese or very obese by WHO standards. Outcomes measured were all-cause death and respiratory-cause hospitalisation and emergency department attendance rate in the following 3 years. Multivariate cox regression modelling was used to estimate hazard ratio (HR) and confidence intervals (CI) adjusted for age, gender, smoking status and FEV1 %predicted. Results: 10, 813 patients were identified (55% male, mean (SD) age 71.07 (±10.48), FEV1 %predicted 59.96% (±19.98%). 1677 deaths (15.5%) occurred during the follow-up period. Compared with individuals with a normal BMI, underweight subjects had a higher mortality risk in adjusted analysis (HR = 1.58, 95% CI = 1.31–1.88). The lowest mortality rates were in overweight subjects (HR = 0.72, 95% CI = 0.64–0.81) and very obese subjects had no significant difference (HR = 0.83, 95% CI = 0.68–1.02, p = 0.08). The relationship between hospitalisation rate and BMI was 'U' shaped. Admission rates were highest in the underweight category where 13.3% of subjects had ≥2 admissions compared to 6.2% and 5.3% of overweight and obese subjects respectively. A similar relationship was observed between BMI and respiratory-cause emergency department attendance. 13.9% of underweight subjects had ≥2 emergency department attendances. The lowest attendance rates were observed in overweight and obese subjects where 6.5% and 5.6% of subjects had ≥2 attendances. Conclusions: Underweight COPD patients have the highest death and hospitalisation rates, whilst being overweight or obese appears to have protective effects. There is potential for nutritional supplementation interventions in underweight COPD patients to improve outcomes, and further research into the protective effects of obesity is required.